Breaking the mold: Socio-ecologic factors to influence the development of non-harsh parenting strategies to reduce risk for child physical abuse. (November 2018) - Fleckman, Julia M.; Taylor, Catherine A.; Storer, Heather L.; Andrinopoulos, Katherine; Weil, Lindsey E.G.; Rubin-Miller, Lily; Theall, Katherine P.
Abstract: Corporal punishment (CP) continues to be a common form of discipline in the U.S despite indications of its long-term harm to children, including strong risk for child physical abuse. Parents that are exposed to CP or physical abuse in childhood are at heightened risk for using CP with their own children. In examining parenting practices relevant to preventing child physical abuse, Positive Deviance relates to those parents who choose effective, positive parenting strategies to discipline their children, despite being exposed to CP and physical abuse in childhood. Little is known about buffering or motivating factors that prevent parents from using CP, or how these factors are influenced by parental childhood history or CP social norms. Therefore, this study examines the motives for use of positive parenting practices, including non-use of CP, for mothers who were exposed to CP and physical abuse in childhood (Positive Deviance). Qualitative interviews were conducted with seventeen mothers with a history of childhood CP and physical abuse. Results indicate that participating mothers believe CP is not an effective discipline strategy and is harmful for children. Mothers opted to use positive parenting practices, rather than CP, with their own children based on empathy, knowledge of harm, as well as rejection of intergenerational transmission of CP and community norms. Findings provide evidence that a Positive Deviance approach can inform target areas for primary prevention strategies aimed at reducing child physical abuse. Directions for multi-level public health prevention approaches and educational campaigns are discussed. Highlights: Participants wanted to shield their children from negative experiences of CP. Practicing self-care promoted the ability to effectively care for children. Direct benefits of positive parenting strategies were identified. Mothers desired to break the intergenerational transmission of CP. Mothers rejected community norms supportive of CP use.